2014
DOI: 10.3389/fpls.2014.00521
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Quercus agrifolia (coast live oak) resistant to the invasive pathogen Phytophthora ramorum in native stands using Fourier-transform infrared (FT-IR) spectroscopy

Abstract: Over the last two decades coast live oak (CLO) dominance in many California coastal ecosystems has been threatened by the alien invasive pathogen Phytophthora ramorum, the causal agent of sudden oak death. In spite of high infection and mortality rates in some areas, the presence of apparently resistant trees has been observed, including trees that become infected but recover over time. However, identifying resistant trees based on recovery alone can take many years. The objective of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
(76 reference statements)
2
25
0
Order By: Relevance
“…Phenolics, such as ellagic acid and a tyrosol derivative, have already been found in the phloem of Quercus agrifolia (coast live oak), another species frequently infected by P. ramorum in the mixed-evergreen forests of California. Surviving coast live oaks appear to have constitutively higher levels of these phenolics than more P. ramorum-susceptible individuals, suggesting the compounds would be good candidates for examination as potential biomarkers for resistance to P. ramorum (Nagle et al, 2011;Conrad et al, 2014). For the same reasons, a greater understanding of what compounds are induced in Japanese larch bark during the early stages of pathogen attack could provide insights into what resistance mechanisms against P. ramorum are already operating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolics, such as ellagic acid and a tyrosol derivative, have already been found in the phloem of Quercus agrifolia (coast live oak), another species frequently infected by P. ramorum in the mixed-evergreen forests of California. Surviving coast live oaks appear to have constitutively higher levels of these phenolics than more P. ramorum-susceptible individuals, suggesting the compounds would be good candidates for examination as potential biomarkers for resistance to P. ramorum (Nagle et al, 2011;Conrad et al, 2014). For the same reasons, a greater understanding of what compounds are induced in Japanese larch bark during the early stages of pathogen attack could provide insights into what resistance mechanisms against P. ramorum are already operating.…”
Section: Discussionmentioning
confidence: 99%
“…Swain et al, 2006) and searching for resistance (e.g. Conrad et al, 2014). Many of these disease-focused studies have been summarized by Kliejunas (2010), but he also concluded that no single strategy is likely to be effective in eradicating P. ramorum, especially once it has established in the wider environment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the rapid screening capacity and ability to detect unforeseen metabolic alterations in biological systems makes FT-IR spectroscopy a suitable technique to be used prior to any targeted metabolite analysis (Chalmers and Griffiths 2002). Nevertheless, the use of FT-IR spectroscopy in woody plant-pathogen interactions is scarce and even more singular when the considering temporal effects (Mart ın et al 2005;Allwood et al 2006;Cameron et al 2006;Martin et al 2007Martin et al , 2008Conrad et al 2014;Vivas et al 2014). So, to our knowledge, this article is the first to describe temporal changes in the metabolic patterns of early interaction between cork oak roots and P. cinnamomi by FT-IR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…; Conrad et al. ). However, because biological systems are composed of a myriad of polymers, macromolecules and metabolites, their infrared spectra are obviously highly complex, comprising the relative contributions from different functional groups, chemical structures and their interactions (Kamnev et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation